Sensory Motor Interventions in the Kinesthetic Development of Autistic Children: Exercise Literature Review - Ira Ocktavia Siagian; Endang Rochyadi; Budi Susetyo; Herlina Hasan (Indonesian Journal of Global Health Research, 2025)
Autism Spectrum Disorder (ASD) is often accompanied by impairment in motor skills and sensory processing, which impacts a child's kinesthetic development. This study aims to examine the effectiveness of sensory motor training interventions in improving the kinesthetic skills of autistic children through a meta-analysis of four national journals in 2021-2023. The four journals include direct interventions in the form of physical exercises, creative media such as batik, and educational game tools Maze Dua Sisi (MADASI). At the time of the journal search the keywords "sensorimotor intervention" AND "autism", "motor development" AND "children with ASD". The results of the analysis showed that sensory motor interventions consistently improved children's movement coordination skills, body balance, fine motor, and independence. The effectiveness of the intervention was strongly influenced by the duration of the exercise, parental involvement, and individual approaches according to the characteristics of the child. This study recommends the integration of sensory motor interventions into the education and nursing services of autistic children as a holistic effort to improve their quality of life. These findings also emphasize the importance of multidisciplinary collaboration and family involvement in supporting ongoing therapy outcomes.